Field Observations During the Third Microwave Water and Energy Balance Experiment (MicroWEX-3): June 16 - December 21, 2004 - Tzu-yun Lin; Jasmeet Judge; Kai-Jen Calvin Tien; Joaquin Casanova; Mi-young Jang; Orlando Lanni; Larry Miller; Fei Yan (EDIS, 2019)
The goal of MicroWEX-3 was to understand the land-atmosphere interactions during the growing season of cotton, and their effect on observed microwave brightness signatures at 6.7 GHz, matching that of the two satellite-based microwave radiometers (AMSR-E and AMSR). This document is Circular 1481, one of a series of the Department of Agricultural and Biological Engineering, UF/IFAS Extension. Original publication date November 2005.